Zgodovinski razvoj kartografije - Fridl, Jerneja (Geografski obzornik, 1995)
The purpose of the article is to represent the development of cartography through the history. Cartography is not closely connected just with geography, but with many other scientific branches as well. The presentation of geographical space and its appearances on maps has been changing through different historical periods according to requirements and knowledge. The historical overview should help us to understand modern cartographical trends of general and thematic map preparation.
Keywords: kartografija; zemljevidi; zgodovinski pregledi